Historical shoreline analysis in selected areas on the east coast of Albay, Philippines - Antonino B. Mendoza Jr.; Joshua K. B. Bista; Skorzeny C. De Jesus; María Luisa U. Tango (Marine and Fishery Sciences)
Shoreline erosion in the Province of Albay, Philippines, remains unmonitored, creating significant vulnerability to natural and anthropogenic drivers. Effective monitoring of coastal integrity is crucial to provide valuable insights into shoreline alterations that can guide future adaptation measures and support climate resilience planning. This study aimed to assess shoreline alterations over the past 20 years by examining natural and anthropogenic drivers shaping these changes and their implications for coastal ecosystems. Erosive trends have resulted in the loss of up to 6 m of coastline in certain places in the cities of Santo Domingo, Bacacay, Malilipot, Legazpi, and Tabaco. Findings revealed that areas distant from river mouths exhibited severe erosion, while those near river mouths showed mixed erosion and deposition patterns. Natural processes, including storm surges and sediment transport, were compounded by human activities such as sand mining, urban expansion, and coastal road constructions, resulting in the degradation, fragmentation and loss of vital coastal ecosystems. These insights underscore the urgent need for systematic shoreline monitoring and the adoption of sustainable coastal management practices, as well as integrating environmental considerations into coastal development planning, enhancing community awareness, and leveraging monitoring data to inform climate resilience and adaptation strategies tailored to local contexts.